Aplicação da técnica de Elipsometria de Emissão para caracterização de materiais luminescentes - Alliprandini Filho, Paulo (2012)
In this work we demonstrated the potential of the emission ellipsometry in the scope of the Stokes theory for electromagnetic field to the photophysics study of luminescent materials, in addition we introduce a new methodology using an achromatic quarter-wave plate. Moreover, the use of linearly polarized light allowed \"selectively\" the study of various photophysical processes, such as the processes related to energy transfer. The use of this technique becomes possible to completely characterize the polarization state of the emitted light for these materials. We show that is possible with the emission ellipsometry study the molecular anisotropy, phase transition, energy transfer processes and solvation. We also verified that the emission ellipsometry technique allows the determination of the molecular alignment direction for anisotropic fluorescent systems, calculate the anisotropy and emission dissymmetry factor. We investigated the emission of dyes dissolved in liquid crystals, showing the effects of molecular alignment on these absorption and emission properties. In addition, we determine the direction of alignment of liquid crystals and the phase transition temperature using the emission ellipsometry technique. We study the emission of poly[2-methoxy-5-((20-ethylhexyl)oxy)-1,4-phenylenevinylene] (MEHPPV) in solution and observed a partially polarized emission, surprising result for an isotropic and homogeneous media and this result is associated with the processes of molecular diffusion. Another material studied was the poly(p-phenylene vinylene) (PPV) where we observed the effect of concentration and size of the counter-ion in casting films, showing that the emission ellipsometry technique allowed to study the carrier diffusion and/or energy transfer processes dependent on the counter-ion. Finally, using the emission ellipsometry technique it was possible investigate the solvents and methacrylates effects on the carrier diffusion and/or energy transfer processes.